2018
DOI: 10.2174/1574888x13666180129164411
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ageing and Gender in Musculoskeletal Stem Cell

Abstract: Advancements in modern technology and experimental techniques have provided an insight into how ageing affects properties of MSCs. However, it is evident that further work needs to be conducted due to many mixed reviews and conflicting data. Given that the human life expectancy is expected to increase the topic of cell ageing and therapeutic applications will remain a hot topic in years to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The donor age has been reported to be associated with deteriorated mitochondrial function in mesenchymal stem cells. 10,12,21,22 Mesenchymal stem cells evaluated in this study were obtained from the adipose tissue of Caucasian female donors with a mean age of 31 years (range 23-39 years). Therefore, differences in age, race, and sex are unlikely to have effects on the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The donor age has been reported to be associated with deteriorated mitochondrial function in mesenchymal stem cells. 10,12,21,22 Mesenchymal stem cells evaluated in this study were obtained from the adipose tissue of Caucasian female donors with a mean age of 31 years (range 23-39 years). Therefore, differences in age, race, and sex are unlikely to have effects on the results.…”
Section: Discussionmentioning
confidence: 99%
“…Factors reported to have effects on characteristics of stem cells include the presence of underlying disease, 9 age, 10 race 11 gender. 12 However, the characteristics of stem cells in the presence of different underlying diseases remain considerably unclear. Nevertheless, a recent study has suggested that the glucose concentration in culture may affect the stem cell characteristics.…”
mentioning
confidence: 99%
“…While the obvious choice may be to isolate and expand autologous SATC, these cells are both limited by availability and age of patient (Ardakani & Khan, 2018; Nurkovic et al., 2016). Therefore, methods to improve proliferation, differentiation, and therapeutic outcomes in aged patients is warranted (Nurkovic et al., 2016).…”
Section: Introductionmentioning
confidence: 99%